Gerencialismo e terceiro setor no estado do Amapá: a parceria público-privado no âmbito do Programa Criança Alfabetizada - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2025)
This research aims to analyze how Public-Private Partnerships (PPP) established in the Literate Child Program in Amapá embody managerialism, privatization, and the commodification of education. This study is guided by the question: how does the performance of the Third Sector, through Public-Private Partnerships in the Literate Child Program in Amapá, manifest the processes of managerialism, privatization, and commodification of education in the context of the neoliberal state? Therefore, the analysis begins by explaining the role of the Third Sector in managing educational policies through PPPs in the neoliberal context. Next,the work identifies the context, origin, foundations, and hierarchical structure of the PCA from the perspective of PPPs. This qualitative research adopted a critical-dialectical perspective to understand the object in its entirety, through documentary analysis of the Literate Child Program and the legislation underlying its creation and implementation. The results indicated that the ongoing state reform legitimizes the hegemony of market logic, leading to privatization, managerialism, and the commodification of educational policies. This materialization occurs through managerial strategies with a strong neoliberal appeal, such as the verticalization of the Collabration Regime, the implementation of Results-Based Management (RBM), and the use of financial incentives (Educational ICMS) and the SisPAEAP as the main device for control, ranking, and accountability. In short, this articulation reveals that the PCA establishes itself as an instrument for consolidating the market logic and the corporatization of education in the context of the state of Amapá. This study contributes to the literature by demonstrating that this situation highlights the concrete reality of managerialism and commodification in a specific regional context, exposing the abandonment of state responsibility and the expansion of private interests.
Keywords: Política Educacional; Educação Pública - Macapá (AP); Avaliação Educacional; CNPQ: CIENCIAS HUMANAS::EDUCACAO::POLITICA EDUCACIONAL; ODS 4 – Educação de qualidade; ODS 16 – Paz, justiça e instituições eficazes; ODS 17 – Parcerias e meios de implementação